2017
DOI: 10.1007/s10334-017-0619-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative effects of acquisition duration and temporal resolution on the measurement accuracy of prostate dynamic contrast-enhanced MRI data: a phantom study

Abstract: Errors in measured wash-in, wash-out, K , and v parameters were minimised using T ≤ 8.1 s and AD ≥ 360 s, with large errors recorded outside of this range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…In the present study, it was found that T res had a strong effect of on certain phenomenological AIF curve‐shape features, namely: TTP1 , TTP2 , P1 , P2 , and Wash‐in Slope (0– TTP1 ), and these errors in AIF measurement were shown to propagate though to errors in certain PK parameter estimations. K trans and k ep values were both strongly affected by the T res , particularly at T res values > 15 s. T res had little effect on the measurement of the AIF Wash‐out Slope (60–360 s), as well as v e estimations; this is in line with previously published works . The use of a LLS regime to fit the standard Tofts model, rather than the more traditionally used NLS approach, was found to almost double the accuracy of K trans estimates, and provided an increase in K trans (intrasession) and k ep (intra‐ and intersession) precision of ~4%.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the present study, it was found that T res had a strong effect of on certain phenomenological AIF curve‐shape features, namely: TTP1 , TTP2 , P1 , P2 , and Wash‐in Slope (0– TTP1 ), and these errors in AIF measurement were shown to propagate though to errors in certain PK parameter estimations. K trans and k ep values were both strongly affected by the T res , particularly at T res values > 15 s. T res had little effect on the measurement of the AIF Wash‐out Slope (60–360 s), as well as v e estimations; this is in line with previously published works . The use of a LLS regime to fit the standard Tofts model, rather than the more traditionally used NLS approach, was found to almost double the accuracy of K trans estimates, and provided an increase in K trans (intrasession) and k ep (intra‐ and intersession) precision of ~4%.…”
Section: Discussionsupporting
confidence: 86%
“…K trans and k ep values were both strongly affected by the T res , particularly at T res values > 15 s. T res had little effect on the measurement of the AIF Wash-out Slope (60-360 s), as well as v e estimations; this is in line with previously published works. [38][39][40] The use of a LLS regime to fit the standard Tofts model, rather than the more traditionally used NLS approach, was found to almost double the accuracy of K trans estimates, and provided an increase in K trans (intrasession) and k ep (intra-and intersession) precision of~4%. The accuracy of the LLS approach was also shown to have lower dependence on the T res used.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, the data were downsampled by discarding frames without changing the image quality. In practice, the longer scan time could be used to improve the SNR, spatial resolution and/or field of view. Larsson et al chose to downsample by averaging frames, leading to improved SNR, and found errors within 15% for temporal resolutions faster than 20 s with the ETM on 101 DCE‐MRI examinations.…”
Section: Discussionmentioning
confidence: 99%
“…No difference was found in the AUC of the ROC curve for the two protocols that diagnosed TZ lesions, although prior research found a higher specificity and accuracy for PI-RADS v2 [28][29][30][31]. Whether DCE could be used in microvascular anatomy and functional evaluation to improve the detection specificity and accuracy for TZ lesions needs further study [32][33][34][35].…”
Section: Diagnostic Performance Comparison In Tzmentioning
confidence: 86%